China’s unfolding Arctic strategy : threatening or opportunistic? - Lasserre, Frédéric; Alexeeva, Olga V.; Huang, Linyan (Minister of National Defence, 2019)
Rapid climatic changes in the Arctic—the fast melting of permafrost, the decline of glaciers, the melting of sea ice—have created perceived strategic and economic opportunities for the littoral states, but have also attracted the attention of states beyond the region. China, for example, without direct access to the Arctic, displays an interest in Arctic research, natural resources, and shipping potential. However, its diplomatic, economic, political and scientific efforts in this region arouse negative reactions among Western media. The media often draw up a portrait of an ambitious and arrogant China, ready to push aside the sovereignty of the Arctic countries to defend Chinese interests in the Arctic. From this perspective, it seems relevant to analyse China’s activities in the region and try to assess Beijing’s strategy in the Arctic, which seems more driven by opportunism than by a long-term desire to challenge the littoral states’ sovereignty. The commercial and strategic implications of climate change and the melting of the sea ice in the Arctic have drawn attention not only of Arctic states but also of some other countries that have no territorial access to the region, such as China and Japan. The growing Chinese interest in the Arctic appears to be a rather recent phenomenon.1 There have been many publications and considerable speculation on that topic, resulting in the construction of an image of a potentially threatening China, which is often described as being very interested in both Arctic mineral resources and the opening of Arctic shipping routes. In addition, China increasingly describes itself as a “near-Arctic” [ ]state,2 as if attempting to legitimize its growing interest in the region. But in this characterization, there is a hint of a perceived threat, as commentators are often stressing that China’s appetite may lead Beijing into considering the Northwest Passage as an international strait, and Arctic resources as up for grabs. Thus, the intensified interest of the world community towards ...